Os imigrantes haitianos, seu cotidiano e osprocessos de territorialização em Cascavel? Paraná - Gaffuri, Evandro Luiz (2016)
I sought with this research understand how through daily practices, the ordinary man "appropriates the territory" in the sense both physical and symbolic, certain territories. Thus, the ordinary man finds himself in this research represented by the figure of Haitian immigrants, who after the disaster of the magnitude 7.0 earthquake on the Richter scale in 2014, began a steady country migration process, making it one of the present foreign nationals in Brazil today. This mobility and greater quantitative presence of Haitians makes normality that territory transmute into other, it allows everyday practices reinvent, which alone guarantees a territorial those immigrants in Brazil. Seeking to identify and understand what factors influence the territorial these immigrants, this research adopted the Life History Method, making several interviews with a total of five Haitians. As a complement to the method, I became a volunteer of an institution that carries out social projects and solidarity, and also it is responsible for the Pastoral do Migrante in Cascavel-PR. I worked in the care of many Haitians, and attend the meetings and meetings as well as in a central role in organizing a special Christmas fellowship for immigrants residing in the city. Data analysis allowed us to understand various factors that influence the process of territorialization of Haitians in Brazil, mong them are: time when the Haitian lives in Brazil; the location of the city and the neighborhood and its inner city relations, capital and the climate; the age at which the Haitian came to Brazil; the perception of women in society; resistance in a fallacious discourse to protect the territory by Brazilian; the presence or absence of family and friends Haitians in Brazil; and resistance in general involving food preparation practices and routine rice and Brazilian beans; the practice of discursive resistance against the government and the Brazilian public service; resistance to make friends, mainly other Haitian friends in Brazil, and finally, the relationship of Brazilian ignore any kind of experience or training of Haitians to serve them, just as hand manual and cheap labor.